Pre-operative immune cell numbers and ratios are associated with peri-operative adverse outcomes in transfused patients - Roets, Michelle; Sturgess, David J.; Chen, Ching-Yu; Punnasseril, Jaisil E. J.; Jones, Lee; van Zundert, Andre A.; Dean, Melinda M. (Frontiers in Anesthesiology, 2024)
Background and objectives Transfusion-related immune modulation (TRIM) and associated adverse outcomes during major surgery are increasingly important to patients and health services internationally. A panel of pre-operative blood tests is an essential part of the pre-operative anaesthetic assessment. This panel of blood tests commonly considers numbers of immune cells (i.e., lymphocytes, monocytes, and neutrophils and cell ratios) that may be used as biomarkers to evaluate and potentially predict post-operative adverse outcomes. Design This retrospective data collection from eight hospital databases, within the Royal Brisbane and Women's Hospital, considered only patients who received blood transfusion during surgery (2016–2018) (n = 2,121). The association between pre-operative immune cell numbers and ratios and adverse outcomes were assessed. Adverse outcomes were coded using the International Classification of Diseases-10 (ICD-10) coding which specifically considered transfusion-related immune modulation. Results were adjusted for confounding factors. Results After adjustment, decreased pre-operative lymphocyte numbers and increased neutrophil/lymphocyte ratio (NLR) were associated with increased odds of developing infection; decreased NLR with decreased odds of developing adverse renal outcomes; and decreased lymphocyte numbers with decreased odds of developing adverse cardiovascular outcomes. Monocyte numbers, neutrophil numbers, and the lymphocyte/monocyte ratio (LMR) were not associated with increased adverse outcomes after adjustment. Conclusion Pre-operative lymphocyte numbers and NLR are associated with adverse outcomes during peri-operative transfusion. Future assessment of peri-operative immune modulation should include the assessment of immune cell function and numbers.